The Student’s Errors on The Use Of Adjectives with The Suffix–Ly : Case Study SMA Negeri 13 Medan - Husnaini Yardas (Institute of Computer Science (IOCS), 2021)
This study deals with student’s errors on the use of adjectives and adverbs with the suffix–ly and regarding adjectives and adverbs identical in form mainly in–ly form and in without–ly form. This survey only investigates them in the written exercises. They cover descriptive adjectives, manner adverbs, intensifying adverbs, and sentence adverbs. The objective of this study is to find out the types and the causes of errors made by student’s on the use adjective and adverbs with the suffix–ly. The sample of this study is 30 student of the third year students of SMA Negeri 13 Medan. This study uses a descriptive quantitative design. The instrument for collecting data consists of a teacher made test in the multiple choice form. The percentage of the student’s errors is dominantly occured in descriptive adjectives from 900 item occurrences, there were 423 errors which categorized into 5 sub categories on the use of adjectives and adverbs with the suffix–ly. Firstly, the use of descriptive adjective was 151 (35,70 %) errors divided into the use with the suffix–ly was 67 (15,84 %) errors and the use without the suffix–ly was 84 (19,86 %) errors. Secondly, the use of manner adverbs was 159 (35,22 %) errors divided into the use with the suffix–ly was 89 (21,04 %) errors and the use without the suffix–ly was 60 (14,18 %) errors. The other one is the use of intensifying adverbs with the suffix–ly was 64 (15,13 %) errors, another one is the use of time adverbs with the suffix–ly was 37 (8,75 %) errors, and the last one is the use sentence adverbs with the suffix–ly was 22 (5,2 %) errors. It is concluded that the errors are due to neglect of rules regarding the use of adjectives and adverbs with the suffix–ly. In short, the errors were dominantly caused by intralingual transfer on the use of adjectives and adverbs with the suffix–ly. It recomended that further in depth studies on the use of adjectives and adverbs with the suffix–ly had be done for the betterment of the teaching-learning process.